Cytocompatibility and bone regeneration potential of chitosan-thiocolchicoside-lauric acid nanogel with insights into zebrafish toxicology - Ameena Mustafa; Meignana Arumugham Indiran; Karthikeyan Ramalingam; Elumalai Perumal; Rajeshkumar Shanmugham; Maria Maddalena Marrapodi; Marco Cicciù; Giuseppe Minervini (Exploration of Medicine)
Aim: The present study explored the bone regeneration potential of chitosan-thiocolchicoside-lauric (CTL) nanogel using MG-63 cell lines. The cytocompatibility of CTL nanogel was also studied using osteoblast-like cells (MG-63 cell lines) and zebrafish embryos. Methods: The effect of CTL nanogel on the metabolic and wound-healing activity of MG-63 cells was investigated in the present study. The alkaline phosphatase (ALP) and bone sialoprotein (BSP) activity of CTL nanogel-treated MG-63 cells were assessed using ELISA. RUNX2, ALP, BSP, and COL1A1 gene expression in MG-63 cells were also investigated after treatment with CTL nanogel. Hatching rates and viability of zebrafish embryos treated with different CTL nanogel concentrations were studied. Any developmental toxicity of embryos after treatment with CTL nanogel was also investigated. Results: There was no significant reduction in the proliferation of MG-63 cells when treated with 5–20 μL/mL of CTL nanogel in the MTT assay (p < 0.05). No prominent morphological changes or nuclear abnormalities were found in the MG-63 cells when treated with various concentrations of CTL nanogel compared to the control group. Invitro scratch wound healing assay showed excellent migration of cells and, hence, showed the excellent wound healing ability of CTL nanogel. ELISA showed significant ALP and BSP activity of CTL nanogel-treated MG-63 cells. RUNX2, ALP, BSP, and COL1A1 gene expression in MG-63 cells after treatment with CTL nanogel were significantly increased compared to the control group (p < 0.05). The hatching and viability rates of the embryos increased as the nanogel concentrations decreased, with the highest hatching rate observed at a 5 µL concentration. Developmental toxicity, such as spinal cord bent, tail bent, or yolk sac oedema, was not observed after treatment with CTL nanogel in zebrafish embryos. Conclusions: CTL nanogel can be used in treating bone defects and helping wound healing. The study also suggests that CTL nanogel had a concentration-dependent effect on zebrafish embryos’ viability and hatching rates only in very high concentrations.